Analisis Pengetahuan Siswa SMAN X Kota Tangerang Selatan Mengenai Konsep Keselamatan dan Kesehatan Kerja (K3) Laboratorium Biologi - Sanusih, Dhea Khoiriyah; Yuliana, Dewi; Haisy, Meilika; Saidah, Nida Haura; Muliyah, Evi (Mahesa Research Center, 2024)
The branch of science that requires students to conduct experiments is Biology. Experiments are carried out in specialized places such as laboratories. To minimize accidents, an understanding of Occupational Safety and Health (OSH) is necessary. This study aims to describe students' knowledge and the completeness of laboratory equipment supporting OSH in the Biology laboratory at SMAN X in South Tangerang City. This research employs qualitative methods through observation, questionnaires, and interviews with biology teachers. Observations show that the laboratory is neatly arranged, equipped with OSH tools such as first aid kits, organic and inorganic waste bins, safety notices, and more. Based on the questionnaire results, it was found that the knowledge of OSH concepts in the Biology laboratory at SMAN X South Tangerang City is quite good. This is evidenced by scores showing results above 8.00.